Hukum Udara Internasional Dalam Kasus Salah Tembak Pesawat Komersial Ukraina Akibat Penembakan Iran Ditinjau Dari Hukum Internasional Dan Konvensi Chicago 1944 - Domas Tomaula; Irma Halima Hanafi; Wilshen Leatemia (Faculty of Law Universitas Pattimura, 2023)
International air law is a collection of regulations made only by a country, which originates from agreements made not only between one country but two or more countries. This agreement can be written and implemented, namely by having a common understanding based on history, so that it has become a common habit that must be accepted. The research method used is normative juridical. Using problem approaches such as the conceptual approach, statutory approach and case approach. Meanwhile, the sources of legal materials used are primary, secondary and tertiary sources of legal materials. The collection of legal materials was carried out by means of a literature study, then analyzed qualitatively. The results of the research show that the regulations for the shooting down of commercial aircraft have been regulated based on International Air Law and the 1944 Chicago Convention article 1 and article 3 bis, countries whose airspace is passed by civil aircraft must guarantee the safety of civil aircraft by establishing a no-fly zone if something is happening in the country's airspace and it is not possible for civil aircraft to pass through as well as providing clear flight navigation so as to guarantee the safety and security of civil aircraft passing through the country's airspace. Iran's form of responsibility for shooting down planes in war is regulated in the 1944 Chicago Convention and other conventions. Iran must take full responsibility for this shooting because it did not establish a no-fly zone when in conflict. In the future, it is necessary to emphasize state responsibility for international civil aviation routes and increase cooperation with various parties so that safety and security in international flights can be achieved.